On the efficiency of the operator splitting method - Faragó, I. (Інститут програмних систем НАН України, 2006)
Operator splitting is a widely used procedure in the numerical solution of complex problems. The point in operator splitting is the
replacement of the original model with one in which appropriately chosen groups of the sub-processes, described by the model, take place
successively in time. This de-coupling procedure allows us to solve a few simpler problems instead of the whole one. In this paper we
investigate the application of the operator splitting method to real-life problems from a practical point of view, with great emphasis on
long-range air pollution transport. We discuss the main benefits and drawbacks of this approach.